Exercise training attenuates angiotensin II-induced vasoconstriction in the aorta of normotensive but not hypertensive rats - Oliveira, Priscila Ramos de; Oliveira, Priscilla Bianca de; Rossignoli, Patrícia de Souza [UNESP]; Spadella, Maria Angélica; Chies, Agnaldo Bruno (Wiley, 2020)
New Findings: What is the central question of this study? What are the effects of exercise on Ang II-induced vasoconstriction in aortas of normotensive rats and how do these effects occur in two-kidney–one-clip hypertensive animals? What is the main finding and its importance? In two-kidney rats, exercise training improves the Ang II-induced vasoconstriction by endothelium-derived NO released through AT2R activation. This effect of exercise training on the Ang II-induced vasoconstriction is blunted in two-kidney–one-clip hypertensive animals, possibly as a consequence of oxidative stress. Abstract: This study investigated the effects of both acute exercise and training on the Ang II-induced vasoconstriction in aorta of normotensive (two-kidney; 2K) and two-kidney–one-clip (2K1C) hypertensive rats, focusing on endothelial mechanisms related to nitric oxide (NO) and prostanoids. Aorta rings of 2K and 2K1C male Wistar rats, sedentary and trained, killed at rest and after acute exercise, were challenged with Ang II in either the absence or the presence of PD 123,319, a selective angiotensin receptor subtype 2 (AT2R) antagonist; Nω-nitro-l-arginine methyl ester (l-NAME), a non-selective inhibitor of nitric oxide synthase; indomethacin, a non-selective inhibitor of cyclooxygenase; or Tiron, an analogue of superoxide dismutase. Aortas of sedentary and trained animals studied at rest were also submitted to histomorphometric analysis. Exercise training reduced the Ang II-induced vasoconstriction in aorta of 2K but not of 2K1C animals. This reduction of Ang II response in aortas of 2K animals was not found after endothelial removal or treatment with PD 123,319 or l-NAME. These results suggest that exercise training improves the modulation of Ang II-induced vasoconstriction in aorta of 2K animals, by endothelium-derived NO released due to the activation of AT2R. No exercise-induced change of Ang II response occurred in 2K1C animals, except in the presence of Tiron, which was evidence for reduction of such responses only in resting trained 2K1C animals. In 2K1C animals, NO modulation of Ang II-induced vasoconstriction might be suppressed by local oxidative stress. Moreover, exercise training slightly reduced the media layer thickness in the aortas of the 2K1C, but not 2K animals, which may indicate cardiovascular protection of these animals.
Keywords: angiotensin II; aorta; exercise